Treatment strategies for the female athlete triad in the adolescent athlete: current perspectives - Thein-Nissenbaum J; Hammer E (Dove Medical Press, 2017)
Jill Thein-Nissenbaum,1 Erin Hammer2 1Department of Family Medicine, University of Wisconsin-Madison, Madison, WI, USA; 2Department of Orthopedics and Rehabilitation, University of Wisconsin-Madison, Madison, WI, USA Abstract: Since the passage of Title IX in 1972, female sports participation has dramatically increased. The benefits of physical activity, including decreased risk for heart disease and diabetes as well as improved body image and self-esteem, far outweigh the risks. However, a select population of adolescent and young adult females may experience symptoms related to the female athlete triad (Triad), which refers to the interrelatedness of energy availability, menstrual function, and bone mineral density (BMD). These conditions often manifest clinically as disordered eating behaviors, menstrual irregularity, and stress fractures; an individual may suffer from 1 or all of the Triad components simultaneously. Because of the complex nature of the Triad, treatment is challenging and requires a multidisciplinary approach. Team members often include a physician, psychologist or psychiatrist, nutritionist or dietitian, physical therapist, athletic trainer, coach, family members, and most importantly, the patient. A thorough physical examination by a primary care physician is essential to identify all organs/systems that may be impacted by Triad-related conditions. Laboratory tests, assessment of bone density, nutritional assessment, and behavior health evaluation guide the management of the female athlete with Triad-related conditions. Treatment of the Triad includes adequate caloric consumption to restore a positive energy balance; this is often the first step in successful management of the Triad. In addition, determining the cause of menstrual dysfunction (MD) and resumption of menses is very important. Nonpharmacologic interventions are the first choice; pharmacologic treatment for MD is reserved only for those patients with symptoms of estrogen deficiency or infertility. Lastly, adequate intake of calcium and vitamin D is critical for lifelong bone health. For this review, a comprehensive search of relevant databases from the earliest dates to July 2016 was performed. Keywords, including female athlete triad, adolescent female athlete, disordered eating, eating disorder, low energy availability, relative energy deficit, anorexia, bulimia, menstrual dysfunction, amenorrhea, oligoamenorrhea, bone mineral density, osteopenia, osteoporosis, stress fracture, and stress reaction, were utilized to search for relevant articles. Articles that directly addressed assessment and management of any 1 or all of the Triad components were included in this comprehensive review. The purpose of this narrative review is to provide the reader with the latest terms used to define the components of the female athlete triad, to discuss examination and diagnosis of the Triad, and lastly, to provide the reader with the latest evidence to successfully implement a multidisciplinary treatment approach when providing care for the adolescent female athlete who may be suffering from Triad-related components. Keywords: energy availability, menstrual dysfunction, bone mineral density, treatment